LaxSr1-xCo0.35Bi0.2Fe0.45O3-δ (x = 0.5 to 0.8): A new series of oxygen separation membrane. (2nd March 2016) - Islam, Q.A.; Raja, M.W.; Basu, R.N.
Abstract: The present study aims to develop a series of novel perovskite based materials with a nominal composition of Lax Sr1-x Bi0.2 Co0.35 Fe0.45 O3-δ (x = 0.5 to 0.8) as oxygen separation membranes. The powder has been synthesized by a soft chemical alanine assisted combustion method. X-ray diffractograms of calcined powders reveal orthorhombic perovskite structure. The optical properties measured by UV-VIS spectroscopy suggest that the variation of lanthanum concentration has mere effect in the electron density as well as band gap of the membranes. Total electrical conductivity as calculated is maximum for the composition with lowest lanthanum concentration (La = 0.5). The permeation flux as measured reveals that the flux generally decreases as the lanthanum concentration increases in the stoichiometry. A highest oxygen permeation flux of 0.23 ml/min/cm 2 has been achieved for the composition La0.5 Sr0.5 Bi0.2 Co0.35 Fe0.45 O3-δ at 900 °C. Graphical abstract: Highlights: Novel composition synthesized using alanine assisted combustion method. Around 99.5% of theoretical density is achieved for sintered membrane. La concentration has mere effect in electron density near Fermi level. High permeation flux has been achieved with 2 mm thick disc membrane. Membranes are highly stable in air & Ar atmosphere at high temperature.